Australian Traineeship System towards a skilled Australia. ([Australia] : Australian Traineeship System, 1980)
Features a photograph of a young man in a bank uniform counting fifty dollar notes.
"Darrin Engelhardt, 17, Bank Trainee, South Australia".
Catalogue record generated as part of a batch load.
Also available online
Keywords: Occupational training -- Australia -- Posters; Youth -- Employment -- Australia -- Posters